Risk factors associated with diabetic foot amputation: A retrospective study from a tertiary hospital in Central Malaysia - Sanjiv Rampal; Claudia Abreu Lopes; Parichehr Hadi; Vasantha Kumari Neela (PLoS ONE, 2026)
Diabetes mellitus continues to escalate as a major global health crisis, with diabetic foot infection (DFI) remaining one of the most serious and preventable complications. Despite advances in multidisciplinary care, amputation rates remain high, particularly in low- and middle-income settings. This retrospective study identifies key predictors associated with the level of amputation; major (above the knee) versus minor (at or below the knee) among patients with DFI following surgical decision-making. Electronic medical records of 434 patients admitted with DFI to a tertiary care hospital in Central Malaysia between January 2010 and December 2019 were analysed. Minor amputations accounted for 70.7% of cases, while major amputations comprised the remainder. Most patients (63.8%) presented with advanced disease, with Wagner grade 4 being the most prevalent (40.3%). Binary logistic regression analysis was employed to determine independent predictors of amputation level. Increasing age (OR = 1.06, p = .013) and higher Wagner classification (OR = 15.16, p < .001) emerged as significant independent predictors of major amputation. These results highlight the need for timely intervention and aggressive limb-salvage strategies in high-risk groups.